Redescription of Tagulis mystacinus (Araneae: Thomisidae) from Sri Lanka - Benjamin, Suresh P.; Jalee, Ziyard (Zootaxa, 2007)
Tagulis mystacinus Simon, 1895 from Sri Lanka is redescribed based on a pair of newly collected male and female specimens. T. mystacinus may be separated from other thomisids by the presence of very peculiar leaf-shaped macrosetae immediately posterior to anterior and posterior lateral eyes. They also may be separated by details of their genitalia.